2016
DOI: 10.1126/sciadv.1500802
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on Earth’s inner core composition inferred from measurements of the sound velocity of hcp-iron in extreme conditions

Abstract: Experimental determination of VP of hcp-Fe can show potential candidates for major light elements in Earth’s inner core.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
63
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 46 publications
11
63
2
Order By: Relevance
“…To meaningfully compare obtained Vp and Vs with PREM, high temperature effects have to be accounted for. At a constant density of 13 g/cm 3 , the T corrections on Vp after experiments by Sakamaki et al (; on hcp‐Fe) and Sakairi et al (; on Fe‐6Si) yield Vp reductions of ∼0.09 m·s −1 ·K −1 , with almost no difference between Fe and Fe‐6Si. Alternatively, by converting the constant pressure simulations of Martorell et al () to a constant density of 13 g/cm 3 , it is possible to estimate the magnitude of anharmonic temperature effects to be ∼0.11 m·s −1 ·K −1 for Fe and Fe3.3Si, and ∼0.05 m·s −1 ·K −1 for Fe‐6.7Si.…”
Section: Discussionmentioning
confidence: 89%
“…To meaningfully compare obtained Vp and Vs with PREM, high temperature effects have to be accounted for. At a constant density of 13 g/cm 3 , the T corrections on Vp after experiments by Sakamaki et al (; on hcp‐Fe) and Sakairi et al (; on Fe‐6Si) yield Vp reductions of ∼0.09 m·s −1 ·K −1 , with almost no difference between Fe and Fe‐6Si. Alternatively, by converting the constant pressure simulations of Martorell et al () to a constant density of 13 g/cm 3 , it is possible to estimate the magnitude of anharmonic temperature effects to be ∼0.11 m·s −1 ·K −1 for Fe and Fe3.3Si, and ∼0.05 m·s −1 ·K −1 for Fe‐6.7Si.…”
Section: Discussionmentioning
confidence: 89%
“…It has been shown that H or C can easily be combined with iron at high pressures (HP) and high temperatures (HT) and could explain such a density deficit (e.g. Fukai, 1984 ;Badding et al, 1991 ;Yagi and Hishinuma, 1995 ;Wood et al, 1996 ;Okuchi, 1997;Saxena A C C E P T E D M A N U S C R I P T Sakamaki et al, 2009 ;Shibazaki et al, 2009Shibazaki et al, , 2011Dasgupta et al, 2009 ;Dasgupta and Hirschmann, 2010 ;Narygina et al, 2011 ;Shibazaki et al, 2012Shibazaki et al, , 2014Sakamaki et al, 2016 ;Iizuka-Oku et al, 2017 ;Dasgupta et al, 2013 ;Lord et al, 2009 ;Tsuno et al, 2018) . However, a recent study of Clesi et al (2018) showed that H is lithophile during core -mantle equilibration and it might be a very minor element in the Earth's core.…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…Experimental and theoretical studies of FeHx suggest that such an iron hydride can satisfy the density and sound velocity of the Earth's core (Hirao et al, 2004;Mao et al, 2004;Sakamaki et al, 2016;Shibazaki et al, 2012;Tagawa et al, 2016). A primary mechanism for including hydrogen into the Earth's core might be through reaction between iron and water during core formation.…”
Section: Geophysical Implicationsmentioning
confidence: 99%